Bone augmentation using a highly porous PLGA/β‐TCP scaffold containing fibroblast growth factor‐2. (26th June 2014) - Yoshida, T.; Miyaji, H.; Otani, K.; Inoue, K.; Nakane, K.; Nishimura, H.; Ibara, A.; Shimada, A.; Ogawa, K.; Nishida, E.; Sugaya, T.; Sun, L.; et al.
Abstract : Background and Objective: Beta‐tricalcium phosphate (β‐TCP), a bio‐absorbable ceramic, facilitates bone conductivity. We constructed a highly porous three‐dimensional scaffold, using β‐TCP, for bone tissue engineering and coated it with co‐poly lactic acid/glycolic acid (PLGA) to improve the mechanical strength and biological performance. The aim of this study was to examine the effect of implantation of the PLGA/β‐TCP scaffold loaded with fibroblast growth factor‐2 (FGF‐2) on bone augmentation. Material and Methods: The β‐TCP scaffold was fabricated by the replica method using polyurethane foam, then coated with PLGA. The PLGA/β‐TCP scaffold was characterized by scanning electron miscroscopy (SEM), transmission electron microscopy (TEM), X‐ray diffraction, compressive testing, cell culture and a subcutaneous implant test. Subsequently, a bone‐forming test was performed using 52 rats. The β‐TCP scaffold, PLGA‐coated scaffold, and β‐TCP and PLGA‐coated scaffolds loaded with FGF‐2, were implanted into rat cranial bone. Histological observations were made at 10 and 35 d postsurgery. Results: SEM and TEM observations showed a thin PLGA layer on the β‐TCP particles after coating. High porosity (> 90%) of the scaffold was exhibited after PLGA coating, and the compressive strength of the PLGA/β‐TCP scaffold was six‐fold greater than that of the noncoated scaffold. Good biocompatibility of the PLGA/β‐TCP scaffold was found in the culture and implant tests. Histological samples obtained following implantation of PLGA/β‐TCP scaffold loaded with FGF‐2 showed significant bone augmentation. Conclusion: The PLGA coating improved the mechanical strength of β‐TCP scaffolds while maintaining high porosity and tissue compatibility. PLGA/β‐TCP scaffolds, in combination with FGF‐2, are bioeffective for bone augmentation.